2014
DOI: 10.1007/s00535-013-0896-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled, double-blind clinical trial of rikkunshito for patients with non-erosive reflux disease refractory to proton-pump inhibitor: the G-PRIDE study

Abstract: There were no significant differences in improvement of GERD symptoms in patients with PPI-refractory NERD between these groups. However, RKT may be useful for improving mental QOL in non-obese patients and acid-related dyspeptic symptoms, especially in women and the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…Several previous studies indicated that upper gastrointestinal symptoms and endoscopic findings were not parallel in patients with reflux esophagitis [5] and non-erosive reflux esophagitis [6][7][8][23][24][25] . This study suggests that the discrepancy between upper gastrointestinal symptoms and endoscopic findings is more common in healthy women in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies indicated that upper gastrointestinal symptoms and endoscopic findings were not parallel in patients with reflux esophagitis [5] and non-erosive reflux esophagitis [6][7][8][23][24][25] . This study suggests that the discrepancy between upper gastrointestinal symptoms and endoscopic findings is more common in healthy women in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The design and primary results of the prospective clinical trial have been previously described elsewhere [16]. This report includes prospectively defined subgroup analyses of clinical characteristics of elderly patients with PPI-refractory NERD from the G-PRIDE study who responded to RKT.…”
Section: Methodsmentioning
confidence: 99%
“…RESQ and the SF-8 correlate moderately well, and the RESQ scores are low when typical GERD symptoms are severe, confirming the discriminatory validity of the RESQ survey. (25) Tominaga et al (26) reported that RPZ + rikkunshito combination therapy improves QOL in PPI-refractory GERD patients. Using the RESQ survey in this study, we demonstrated that the addition of rikkunshito also improved QOL related to meals and sleep.…”
Section: Discussionmentioning
confidence: 99%